PWE-186 Effective, Safe Management of Starved Patients with Anorexia Nervosa through a Combined Medical & Psychiatric Approach-Meeting the Marsipan Challenges. (4th June 2013) - Perowne, R; Wells, C; Temple, M; Kannan, D
Abstract : Introduction: Anorexia Nervosa (AN) has the highest mortality rate of any psychiatric condition. These patients are a challenge to manage because of severe physical and psychiatric morbidity. MARSIPAN reported that some patients with severe AN admitted to medical wards were deteriorating & occasionally dying because of delays in treating their medical conditions due to obstructive behaviours relating to their psychiatric morbidity 1 . It recognised a need for specialist teams including a psychiatrist and physician with an interest in eating disorders. There is a medical team providing in-patient medical management at University Hospital North Tees (UHNT) with support from the community eating disorders (ED) team. Methods: A retrospective audit of management of AN admissions due to starvation (BMI 13 or less) to UHNT June 2010-June 2012. Data collected from medical notes-audited against MARSIPAN standards. Results: 10 patients identified, all female. Age 18–43 (median 24.5). 9 known to ED service. Median admission BMI 12.8 (9.7–13). Assessment: All had recommended blood tests. 8 had an ECG; 2 abnormal (long QTc, heart block). Monitoring: 9 had appropriate electrolyte monitoring. All weighed twice weekly & had complete fluid balance charts. Management: 8 seen by ED physician within 48 hours (5 within 24 hrs), 6 seen by dietitian by 48 hours. All received pabrinex, 9 vitamin B & multivitamins. 4 did not receive DVT prophylaxis. All reviewed at least weekly by psychiatric ED team. 7 NG fed, 4 began NG feed within 24 hours, all established by 48 hours. 7 required electrolyte replacement. Complications: Re-feeding syndrome (7), pneumonia (2), ITU admissions (2; pneumonia, abnormal electrolytes). 3 exhibited problematic behaviour; 2 required 1 to 1 nursing. All complications recognised early. Discharge: All had discharge plans agreed by the ED team, 5 discharged to the ED unit. Conclusion: The ED team at UHNT provides a successful specialist service for the medical care of patients with severe AN. A median admission BMI of 12.8 indicated early identification & intervention of at risk community patients through this integrated approach. Patients are appropriately assessed & monitored & NG feeding is quickly established. Management of these patients by the multidisciplinary team enables the medical and behavioural challenges to be dealt with effectively and ensures timely discharge once medically stable. Through the development of trust guidelines we hope to further improve care of this vulnerable group. Disclosure of Interest: None Declared. Reference: MARSIPAN: Management of Really Sick Patients with Anorexia Nervosa, College Report 162, Royal College of Psychiatrists and Royal College of Physicians London, October 2010